Fabella fracture with radiological imaging: A case report. (December 2017) - Zhou, Feng; Zhang, Fei; Deng, Guoying; Bi, Chun; Wang, Jiandong; Wang, Qian; Wang, Qiugen
Abstract: The fabella is a kind of sesamoid bone which is located in the lateral head of the gastrocnemius muscle. A slice of studies demonstrated that fabella is involved in the knee joint stabilization. Fabella fracture may cause knee pain or functional impairment as the previous reports pointed. It is extremely rare, which leads to its high rate of missed diagnosis in clinical and radiography to some extent. We report a case of a 38-year-old female who was struck by an electromobile. The fabella fracture was confirmed on X-ray plain films. After that, the degree of injury was evaluated with the magnetic resonance imaging (MRI).